Shadows and rings of the Kehagias-Sfetsos black hole surrounded by thin disk accretion. Issue 6 (18th June 2021) - Li, Guo-Ping; He, Ke-Jian
Abstract: In this paper, under the illumination of thin disk accretion, we have employed the ray-tracing method to carefully investigate shadows and rings of the Kehagias-Sfetsos(KS) black hole in deformed Hořava-Lifshitz(HL) gravity. The results show that the event horizon r+, the radius r_p and impact parameter bp of photon sphere are all decreased with the increase of the HL parameter ω, but the effective potential increases. And, it also turns out that the trajectories of light rays emitted from the north pole direction are defined as the direct emission, lensing ring and photon ring of KS black hole, on the basis of orbits n = ϕ/2π. As black hole surrounded by thin disk accretion, we show that the corresponding transfer functions have their values increased with the parameter ω. More importantly, we also find that the direct emissions always dominate the total observed intensity, while lensing rings as a thin ring make a very small contribution and photon ring as a extremely narrow ring make a negligible contribution, for all three toy-model functions. In view of this, the results finally imply that shadows and rings as the observational appearance of KS black hole exhibit some obvious interesting features, which might be regarded as an effective way to distinguish black holes in HL gravity from the Schwarzschild black hole.